The Future of Nuclear Security in Moroccan Territory After the Creation of the New Moroccan Agency of Nuclear and Radiological Safety and Security: Opportunities and Challenges - Amal Touarsi; Amina Kharchaf (International Journal of Nuclear Security, 2017)
Nowadays, a security regime for protecting nuclear and radiological material—providing an intelligent national regulatory institution and establishing national security laws—is necessary in order for a state to ensure security of nuclear and radiological materials used within its borders. This paper focuses on discussing the opportunities and challenges facing the future of nuclear security after the creation of the new Moroccan Agency of Nuclear and Radiological Safety and Security.
Keywords: Nuclear Security; Transport; Radioactive Materials; Safety; Regulations